Pengaruh Motivasi, Kepemimpinan, Disiplin Kerja Terhadap Kinerja Karyawan Nekata Printing Tangerang - Mohammad Zuhri (Jurnal Syntax Transformation, 2022)
This study aims to describe the problems in Nekata Printing where the development of the printing service business sector is an opportunity for small companies for sub-sectoral work. Taking advantage of opportunities to reach consumers, creating competition between similar printing service companies. This also makes every company innovate creative marketing strategies to sell the services offered to the target audience. Nekata Printing is a service company founded in 2013 and is engaged in printing services. The obstacle that often occurs is when the project work schedule is in this condition. The need for leadership direction, company motivation, and good work discipline between work fields at Nekata Printing can be followed up on employee performance as soon as possible not to cause disappointment from consumers. Based on the description above, the authors are interested in conducting research written in the form of scientific writing entitled "The Effect of Motivation, Leadership and Work Discipline on the Performance of Nekata Printing Employees".